Color Detector in an Image using Python and Computer Vision Library - Ardianto, Dicky; Widiyatmoko, Arif Tri (Apik Cahaya Ilmu, 2024)
This research explores the implementation of a color detection system in images using the Python programming language and the Computer Vision library. The primary aim is to enhance the accuracy and efficiency of color detection, a critical component in the realm of automated systems and artificial intelligence. Leveraging Python's versatility and the specialized features of the Computer Vision library, the study conducts experiment to evaluate the proposed system's reliability across diverse image contexts and lighting conditions. The literature review encompasses fundamental color detection concepts, recent advancements in Computer Vision, and practical applications from prior relevant research. The anticipated outcome of this research is a substantial contribution to advancing our understanding of color detection within image processing, with potential implications for a more reliable and widely applicable system